Analysis of Transparency, Accountability and Community Participation in Village Fund Financial Management - Tendri soli; Agustina Mutia; Ferri Saputra Tanjung (Faculty of Islamic Economics and Business, State Islamic University Sunan Kalijaga, 2026)
Purpose: This study aims to explore how transparency, accountability, and community participation in the financial management of the Village Fund are implemented in Simbur Naik Village, East Muara Sabak District. Methodology: This study uses a qualitative method. Data were obtained through interviews, observations, and documentation with informants, including village heads, village secretaries, finance heads, members of the Village Consultative Body, and community members. The data collection and analysis process consists of the stages of data reduction, data display, and conclusion making. Findings: The results of the study show that the village government has tried to implement the principles of transparency and accountability through the publication of information and the preparation of accountability reports. However, the implementation is not optimal, and public participation is still low. From the perspective of sharia accounting, the management of the Village Fund reflects the values of trust, honesty, responsibility, and justice as a form of accountability not only to the community but also to realize the common good. To achieve more efficient village financial governance, information quality must be improved, accountability strengthened, and community participation expanded. Novelty: This research advances holistic governance that balances upward, downward (community), and outward (divine) accountability. This research uses a triangulated Lens from Stewardship Theory, Good Governance, and the Sharia Accounting perspective. Finally, the Qualitative view distinguishes between formalistic publication and substantive community understanding.